Perlindungan Hukum Terhadap Anak Di LingkunganProduksi Dan Pengkonsumsi Miras (Studi Kasus di Wilayah Sukoharjo dan Polres Sukoharjo) - Pratama, Sandro Cahyo; , Hartanto, SH, M.Hum; , Bambang Sukoco S.H.,M.H (2016)
This study aims to determine the legal protection and reality related to the presence of children in the location of producers and consuming alcohol in the region and efforts Sukoharjo Police in their protection. The method used is empirical juridical with descriptive research. The data source consists of primary data, interviews and secondary data is data of primary and secondary law. Data were collected by literature study and interviews and then analyzed qualitatively. The results showed the legal protection of children stipulated in the Child Protection Act No. 35 of 2014 Article 20 to include government, parents, and community. Reality suggests children and consuming alcohol blend live in a community where there are people or adults who allow and less care about the negative impact of the environment, so that there are children who went along to consume alcohol. Efforts Police in child protection that is by working with the community in the form of socialization and empowers communities to manage their own cases circulation of alcohol in the environment in accordance with applicable law, also in cooperation with educational institutions with socialization and training and the prevention of children from the influence of alcohol and always conduct security patrols to minimize crime will occur.